Age‐Related Changes and Effects of Bisphosphonates on Bone Turnover and Disease Progression in Fibrous Dysplasia of Bone. (15th January 2019) - Florenzano, Pablo; Pan, Kristen S; Brown, Sydney M; Paul, Scott M; Kushner, Harvey; Guthrie, Lori C; de Castro, Luis Fernandez; Collins, Michael T; Boyce, Alison M
ABSTRACT: Fibrous dysplasia (FD) is a mosaic disease in which bone is replaced with fibro‐osseous tissue. Lesions expand during childhood, reaching final burden by age 15 years. In vitro data suggest that disease activity decreases in adulthood; however, there is no clinical data to support this concept. Bone turnover markers (BTMs) have been used as markers of disease activity in FD; however, the natural history of BTM changes, the effects of antiresorptive treatment, and their association to clinical outcomes have not been described. The goals of this study are to describe 1) the natural history of FD disease activity and its association with pain; 2) the impact of bisphosphonates on the natural history of BTMs; and 3) the effect of bisphosphonates on progression of FD burden during childhood. Disease burden scores and alkaline phosphatase, osteocalcin, NTx, FGF23, and RANKL levels from 178 subjects in an FD/MAS natural history study were reviewed, including 73 subjects treated with bisphosphonates. BTMs, RANKL, and FGF23 demonstrated a sustained reduction with age. Bisphosphonate treatment did not significantly impact this age‐dependent decrease in BTMs. Pain was more prevalent and severe in adults compared with children and was not associated with BTMs. In children, the progression of disease burden was not affected by bisphosphonates. In conclusion, FD is associated with an age‐dependent decline in bone turnover and other markers of disease activity. Pain, in contrast, is more frequent and severe in adults with FD and is not related to bone turnover. Bisphosphonate treatment does not significantly impact the age‐dependent decrease in bone turnover, nor does it prevent the progression of FD disease burden in children. These findings, in association with the established adverse effects of antiresorptives, should be considered when evaluating use and response to bisphosphonates in patients being treated for FD and in any study using BTMs as surrogate endpoints. © 2019 American Society for Bone and Mineral Research.